Bond strength of orthodontic brackets using the anti-bacterial primer, Denteshield® - Murphy Craig; Xu Xiaoming; Yu Qingzhao; Armbruster Paul; Ballard Richard (Australasian Orthodontic Journal, 2023)
This study examined the bond strength associated with Denteshield® Primer as a replacement for a conventional, non-antimicrobial, orthodontic primer.